Determinants of tax avoidance: Evidence from Indonesian mining industry - Sulistiyanti, Umi; Dwi Saputra, Aristianto (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2020)
Tax avoidance is one of the company strategies to alleviate the company's tax burden by minimizing the amount of tax that must be paid legally. The mining sector is the most vulnerable sector to practice tax avoidance because this sector gains large profits from the mining activities carried out. This study aims to empirically examine the influences of executive incentive, corporate risk, corporate governance, and accounting conservatism on tax avoidance. The research population of this study was mining companies listed in the Indonesia Stock Exchange (IDX) from 2012 to 2017 as many as 41 companies. These research samples were 5 companies or 30 observation data selected by purposive sampling method. The data used is secondary data which is then analyzed using multiple regression. The result of the research showed that audit quality and accounting conservatism had negatively significant effects on tax avoidance. Meanwhile, executive incentive, corporate risk, institutional ownership, independent commissioners, and audit committee did not effect on tax avoidance.